ISLAMIC ECONOMIC CONCEPT AS A SOLUTION TO THE PROBLEMS OF CAPITALIST ECONOMY - Muslih, M Kholid; Indallah, Sayyid Muhammad (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
The capitalist economic system according to Karl Marx has shortcomings, according to him there is oppression between classes which causes humans to lose their existence. Then, Karl Marx proposed a solution by introducing a socialist economic system. However, it should be noted that the proposed solution does not concretely solve the existing problems. The concept exists in the theoretical realm and is difficult to implement in real practice. Therefore, an economic system approach is needed that can effectively respond to and address the existing problems. This paper aims to explain the criticism of Karl Marx's concept of alienation as a solution to the capitalist economic system. In compiling this article, the author uses a critical analytical method. The results of this study state that, Karl Marx with the concept of alienation tried to restore human existence caused by conflict between classes in the capitalist economic system. Because, in the capitalist economic system, workers become alienated from work products, the environment, and the nature of their work. The problem in the capitalist economic system is that humans are divided into two parts, namely the owners of capital and the workers who sell their labor to them. Thus, the solution to the oppression of the proletariat over the workers is class liberation or common ownership. However, this is contrary to Islam. Because Karl Marx's idea of alienation is atheistic, contradictory, and unacceptable to common sense. Therefore, Karl Marx's concept of socialist alienation cannot be a solution to the capitalist economic system.